Exploring the Consumption Value for Halal Cosmetics Purchase Intention: A Proposed Conceptual Framework - Liew, Christine Wan-Shean; Karia, Noorliza (Journal of Entrepreneurship, Business and Economics, 2024)
Despite the negative sustainability consequences from conventional cosmetics, many Malaysian consumers continue using them. With unsustainable issues being widely reported and must be addressed by consumers’ adoption of Halal cosmetics with sustainable attributes. Therefore, the purpose of this paper is to develop a conceptual framework to investigate factor influencing consumers’ intention to purchase Halal cosmetics in Malaysia. Theory of consumption value (TCV) was employed as an underpinning theory, utilizing unique context-specific attributes of Halal cosmetics to aid in the development of the conceptual framework. A quantitative analysis with electronic questionnaire survey is proposed as data collection process. This paper makes significant theoretical contributions by integrating the unique context-specific attributes associated with the consumption values of Halal cosmetics, highlighting the novelty of this conceptual framework. The proposed conceptual framework also serves as a reference and guidance for Halal cosmetics manufacturers, marketers, and policymakers that seek to formulate marketing and policy strategies aimed at motivating consumers to actively purchase Halal cosmetics. This, in turn, can contribute to the pursuit of sustainable development and expansion of the Halal cosmetics market in Malaysia Conceptual paper Keywords: Halal cosmetics; Sustainability; Consumption value; Theory of consumption value; Purchase intention Reference to this paper should be made as follows: Liew, C. W.-S., & Karia, N. (2023). Exploring the Consumption Value for Halal Cosmetics Purchase Intention: A Proposed Conceptual Framework. Journal of Entrepreneurship, Business and Economics , 11 (2), 130–167.